Angiotensin 1-7 alleviates aging-associated muscle weakness and bone loss, but is not associated with accelerated aging in ACE2-knockout mice. (24th September 2019) - Nozato, Satoko; Yamamoto, Koichi; Takeshita, Hikari; Nozato, Yoichi; Imaizumi, Yuki; Fujimoto, Taku; Yokoyama, Serina; Nagasawa, Motonori; Takeda, Masao; Hongyo, Kazuhiro; Akasaka, Hiroshi; Takami, Yoichi; et al.
Abstract : The angiotensin-converting enzyme 2 (ACE2)-angiotensin 1-7 (A1-7)-A1-7 receptor (Mas) axis plays a protective role in the renin–angiotensin system (RAS). We recently found that ACE2 knockout (ACE2KO) mice exhibit earlier aging-associated muscle weakness, and that A1-7 alleviates muscle weakness in aging mice. In the present study, we investigated the role of the A1-7-Mas pathway in the effect of ACE2 on physiological aging. Male wild-type, ACE2KO, and Mas knockout (MasKO) mice were subjected to periodical grip strength measurement, followed by administration of A1-7 or vehicle for 4 weeks at 24 months of age. ACE2KO mice exhibited decreased grip strength after 6 months of age, while grip strength of MasKO mice was similar to that of wild-type mice. A1-7 improved grip strength in ACE2KO and wild-type mice, but not in MasKO mice. Muscle fibre size was smaller in ACE2KO mice than that in wild-type and MasKO mice, and increased with A1-7 in ACE2KO and WT mice, but not in MasKO mice. Centrally nucleated fibres (CNFs) and expression of the senescence-associated gene p16INK4a in skeletal muscles were enhanced only in ACE2KO mice and were not altered by A1-7. ACE2KO mice, but not MasKO mice, exhibited thinning of peripheral fat along with increased adipose expression of p16INK4a . A1-7 significantly increased bone volume in wild-type and ACE2KO mice, but not in MasKO mice. Our findings suggest that the impact of ACE2 on physiological aging does not depend on the endogenous production of A1-7 by ACE2, while overactivation of the A1-7-Mas pathway could alleviate sarcopenia and osteoporosis in aged mice.